Effects of ultrasound on functional properties, structure and glycation properties of proteins: a review. Issue 15 (22nd August 2021) - Lin, Derong; Zhang, Qiuting; Xiao, Lijuan; Huang, Yichen; Yang, Zhengfang; Wu, Zhijun; Tu, Zongcai; Qin, Wen; Chen, Hong; Wu, Dingtao; Zhang, Qing; Li, Suqing
Abstract: Protein is an indispensable part of life. It provides nutrition for human body and flavor for food. The role of protein depends largely on the functional properties of the protein. Therefore, the elucidation of protein structure and functional properties needs to be further explored. The effects of structural and functional properties of proteins under different ultrasonic treatment conditions were reviewed. The structural changes of protein were studied by hydrogen–deuterium exchange mass spectrometry combined with fluorescence spectrometry and proteomics, and the mechanism of action was determined. The glycation site, the glycation degree, and the glycation characteristics of different sugars were determined. The protein was modified by ultrasound, and the influence of protein structure, physicochemical properties, protein glycation characteristics, and the action mechanism were analyzed by biological mass spectrometry.